Papillon–Lefèvre Syndrome: A Report of Four Cases in One Family - Çege, Muhammed Abdullah; Çankal, Dilek Aynur; Binici, Ebru; Turhan Bal, Bilge (Journal of Dentistry Indonesia, 2025)
Papillon–Lefèvre syndrome (PLS) is a rare genetic disorder caused by mutations in the cathepsin C gene and inherited in an autosomal recessive pattern. The risk of its occurrence is heightened by consanguineous marriages. PLS affects both genders and presents with hyperkeratotic patches on the hands and feet and precocious aggressive periodontitis. Although teeth initially erupt normally, rapid resorption in periodontal tissues leads to swift tooth loss, and prosthetic rehabilitation is complicated due to aggressive alveolar bone resorption. Case report: In 2021, a brother and sister sought dental treatment at Gazi University’s Faculty of Dentistry. After thorough examinations, the brother underwent total teeth extraction and subsequently received prosthetic treatment, while the sister opted for a removable prosthesis post-extraction. Two years later, the brother’s prosthesis showed no issues, justifying its continued use. However, the sister required a total prosthesis after total teeth extraction. Regular check-ups are essential for both patients, as they are candidates for dental implants after growth and development completion. Conclusion: It is important to note that PLS is a rare condition; therefore, vigilant dental diagnosis and effective management are crucial.